2007
DOI: 10.1097/01.ogx.0000256787.04807.da
|View full text |Cite
|
Sign up to set email alerts
|

Combined Vitamin C and E Supplementation During Pregnancy For Preeclampsia Prevention: A Systematic Review

Abstract: After completion of this article, the reader should be able to recall that many methods have been used to prevent preeclampsia, state that increased oxidative stress has been postulated and many trials have used antioxidants to prevent the disease, and explain that MEDLINE analysis of the literature questions the use of vitamin C and E supplements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 7 publications
1
39
0
3
Order By: Relevance
“…With oxidative stress being widely implicated in pathophysiological pregnancy, attention has been focused on the potential benefits of other antioxidant dietary interventions, such as vitamins C and E and selenium. Vitamin C and E supplementation reduces the levels of circulating markers of endothelial activation and lipid peroxidation (Chappell et al 2002); however, meta-analyses have failed to demonstrate that this provides any clinical benefits (Rumbold & Crowther 2005a, 2005b, Polyzos et al 2007, Roberts et al 2010 and may even increase the rates of adverse pregnancy outcomes (Poston et al 2006, Klemmensen et al 2009). Clinical studies of selenium supplementation, an important component of the antioxidant glutathione peroxidase, in pregnancy are still awaited.…”
Section: Discussionmentioning
confidence: 99%
“…With oxidative stress being widely implicated in pathophysiological pregnancy, attention has been focused on the potential benefits of other antioxidant dietary interventions, such as vitamins C and E and selenium. Vitamin C and E supplementation reduces the levels of circulating markers of endothelial activation and lipid peroxidation (Chappell et al 2002); however, meta-analyses have failed to demonstrate that this provides any clinical benefits (Rumbold & Crowther 2005a, 2005b, Polyzos et al 2007, Roberts et al 2010 and may even increase the rates of adverse pregnancy outcomes (Poston et al 2006, Klemmensen et al 2009). Clinical studies of selenium supplementation, an important component of the antioxidant glutathione peroxidase, in pregnancy are still awaited.…”
Section: Discussionmentioning
confidence: 99%
“…70 Given the abnormally low plasma vitamin C concentrations reported in preeclampsia, a combination of vitamins C and E has been postulated as a prophylactic strategy for prevention of preeclampsia. 71 However, there is no evidence that high doses of vitamin C and vitamin E (1000 mg and 400 IU, respectively) combined reduce the occurrence of preeclampsia. 72 In particular, some randomized controlled trials involving a large number of pregnant women have shown a lack of benefit in women receiving antioxidants, 73e76 as reported in Table 1.…”
Section: Role Of Antioxidants In Preeclampsiamentioning
confidence: 99%
“…Recent meta-analysis of all eligible vitamin C and E supplementation trials in preeclampsia has concluded that "the available evidence does not support the combined vitamin C and E supplementation during pregnancy for the prevention of preeclampsia." 35 With the overwhelming evidence of increased oxidative stress during preeclampsia, the reasons for lack of beneficial effects of antioxidant vitamins are unclear. Possible explanations for these inconsistencies could be differences in study population and criteria for patient selection, etc.…”
Section: Hoffmann Et Al Tempol Ameliorates Preeclampsia In Bph/5 Micementioning
confidence: 99%